BACKSCATTERING FROM A CUBE - Ludwig, A. C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Three analytical techniques -- the method of moments, geometrical theory of diffraction, and physical optics (without fringe current correction) -- are applied to the case of backscattering from a cube. Results are compared to experimental data. It is relatively easy to compute specular scattering with good accuracy; it is much more difficult to obtain good accuracy for corner incidence, which is emphasized here precisely because it provides a more rigorous test of an analytical technique. As expected, the method of moments provides good results when the segmentation is on the order of 0.1 wavelengths, and in some cases up to 0.26 wavelengths. Single-diffraction geometrical theory of diffraction predicts peak scattering within a few dB for a cube dimension of 0.1-3 wavelengths, which is the full range of experimental data, but is not accurate between peaks. Physical optics predictspeak scattering within a few dB for a cube dimension of 1-3 wavelengths, and is also not accurate between peaks. [Vol. 2, No. 2 pp. 55-74 (1987)]